A deep learning approach to visualize aortic aneurysm morphology without the use of intravenous contrast agents - Chandrashekar, A; Handa, A; Lapolla, P; Shivakumar, N; Uberoi, R; Grau, V; Lee, R (Lippincott, Williams & Wilkins, 2023)
Background: Intravenous contrast agents are routinely used in CT imaging to enable the visualization of intravascular pathology, such as with abdominal aortic aneurysms. However, the injection is contraindicated in patients with iodine allergy and is associated with renal complications.